Determination of Relationship between Some Ud der and Body Traits of Holstein Cows by Canonical Correlation Analysis - Alıç Ural, Deniz; Barutçu, İlkay (Afyon Kocatepe Üniversitesi, 2013)
The purpose of the research was to obtain the relationship between some udder and body traits. In an attempt to perform the study, canonical correlations among height at withers (HW), shinbone perimeter (SP), body length (BL), chest girth (CG), stature (S), rump width (RW), rear udder height (RUH), right fore udder teat perimeter (RFUTP), right rear udder teat perimeter (RRUTP),left fore udder teat perimeter (LFUTP), left rear udder teat perimeter (LRUTP), fore udder teat length (FUTL), and rear udder teat length (RUTL) in 50 head Holstein cows that were raised at a dairy farm in Bozdogan province in Aydin county, were estimated. Six body traits constituted the X variable set while seven udder traits constituted the Y variable set. As a result, the correlation between the first canonical variable pair was found 0.62 (P> 0.05). The contribution occurrences of canonical variables of HW and BL from body traits and LRUTP and RRUTP from udder traits were found the highest than others. According to these results, the degrees of explanation (redundancy) of change on each other of the two variable sets (U1 and V1) were found 6.2 % and 2.1 %, respectively.

Bu çalışmanın amacı, bazı meme özellikleri ile vücut özellikleri arasındaki ilişkinin ele alnımasıdır. Bu amaçla, Aydın ilinin Bozdoğan ilçesinde bulunan bir süt sığırcılığı işletmesinde yetiştirilen 50 baş Holştayn inekte cidago yüksekliği (CY), incik çevresi (İÇ), vücut uzunluğu (VU), göğüs çevresi (GÇ), sağrı yüksekliği (SY), sağrı genişliği (SG), arka meme yüksekliği (AMY), sağ ön meme başı çevresi (SÖMBÇ), sağ arka meme başı çevresi (SAMBÇ), sol ön meme başı çevresi (SLÖMBÇ), sol arka meme başı çevresi (SLAMBÇ), ön meme başı uzunluğu (ÖMBU) ve arka meme başı uzunluğu (AMBU) arasındaki kanonik korelasyonlar tahmin edilmiştir. 7 meme özelliği Y değişken seti olarak alınırken, 6 vücut özelliği de X değişken seti olarak alınmıştır. Sonuçta, birinci kanonik değişken çifti arasındaki korelasyon 0.62 olarak bulunmuştur (P> 0.05). Vücut ölçülerinden CY ile VU, meme SLAMBÇ ile SAMBÇ’ye ait kanonik değişkenlerin yaptığı katkı diğerlerine göre daha yüksek bulunmuştur. Elde edilen sonuçlara gore, iki değişken setinin (U1 ve V1) birbiri üzerindeki değişimi açıklama derecesi (gereksizlik indeksi) sırasıyla % 6.2 ile % 2.1 bulunmuştur.
Kanonik Korelasyon Analizi ile Holştayn ineklerin Bazı Meme ve Vücut Özellikleri Arasındaki İlişkinin Saptanması
Keywords: Body and Udder Measurements; Canonical Correlations Holstein; Cows